Neonatal Chest Wall Rhabdomyosarcoma - Michael Feldman; Zvi Steiner; Gabriel Groisman; Erez Nadir (Georg Thieme Verlag KG, 2015)
Abstract An infant was born at term with a huge chest mass diagnosed as rhabdomyosarcoma. Treatment consisted of surgical resection and chemotherapy. We describe this very rare congenital mass and the problematic therapeutic management of such a tumor in a newborn.